Mammalian target of rapamycin inhibition impacts energy homeostasis and induces sex‐specific body weight loss in humans - Marwan Mannaa; Pia Pfennigwerth; Jens Fielitz; Maik Gollasch; Michael Boschmann (Wiley, 2023)
Abstract Background Previous data from a 2‐year randomized controlled trial (CRAD001ADE12) indicated that mammalian target of rapamycin (mTOR) inhibition by everolimus slowed cyst growth in patients with autosomal‐dominant polycystic kidney disease (ADPKD). During the trial, we noted body weight loss in some patients, particularly in women. We hypothesized that everolimus causes body weight reduction by reduced food intake and/or metabolic changes, which could lead to cachexia. Methods Within a sub‐analysis of the CRAD001ADE12 trial, body weight course was investigated regarding sex‐specific differences in 433 adult ADPKD patients (everolimus, n = 215; placebo, n = 218). One hundred four out of 111 patients who participated in the clinical trial centre in Berlin were evaluated under everolimus/placebo therapy (on drug: everolimus, n = 48; placebo, n = 56) and after therapy (off drug: everolimus, n = 15; placebo, n = 18). Eating habits and nutrient/caloric intake were evaluated by validated questionnaires. Systemic and local metabolism was evaluated in four patients after an oral glucose load (OGL) by using calorimetry and adipose/muscle tissue microdialysis. Results Within the 2‐year CRAD001ADE12 trial, a significant body weight loss was observed in female patients on everolimus versus placebo (P = 0.0029). Data of the Berlin Cohort revealed that weight loss was greater in women on everolimus versus men (P < 0.01). After 9 months, women and men had lost 2.6 ± 3.8 and 0.8 ± 1.5 kg (P < 0.05) in body weight, respectively, and after 21 months, they had lost 4.1 ± 6.6 and 1.0 ± 3.3 kg (P < 0.05), respectively. On everolimus, caloric intake was significantly lower in women versus men (1510 ± 128 vs. 2264 ± 216 kcal/day, P < 0.05), caused mainly by a lower fat and protein intake in women versus men. Cognitive restraints, disinhibition and hunger remained unchanged. In a subgroup of patients resting metabolic rate was unchanged whereas OGL‐induced thermogenesis was reduced (7 ± 2 vs. 11 ± 2 kcal, P < 0.05). Fasting and OGL‐induced fat oxidation was increased (P < 0.05) on versus off everolimus. In adipose tissue, fasting lipolytic activity was increased, but lipolytic activity was inhibited similarly after the OGL on versus off everolimus, respectively. In skeletal muscle, postprandial glucose uptake and aerobic glycolysis was reduced in patients on everolimus. Conclusions mTOR inhibition by everolimus induces body weight reduction, specifically in female patients. This effect is possibly caused by a centrally mediated reduced food (fat and protein) intake and by centrally/peripherally mediated increased fat oxidation (systemic) and mobilization (adipose tissue). Glucose uptake and oxidation might be reduced in skeletal muscle. This could lead to cachexia and, possibly, muscle wasting. Therefore, our results have important implications for patients recieving immune‐suppressive mTOR inhibition therapy.